A JAZ Protein in Astragalus sinicus Interacts with a Leghemoglobin through the TIFY Domain and Is Involved in Nodule Development and Nitrogen Fixation - Li, Yixing; Xu, Meng; Wang, Ning; Li, Youguo (PloS one, 2015)
Leghemoglobins (Lbs) play an important role in legumes-rhizobia symbiosis. Lbs bind O2 and protect nitrogenase activity from damage by O2 in nodules, therefore, they are regarded as a marker of active nitrogen fixation in nodules. Additionally, Lbs are involved in the nitric oxide (NO) signaling pathway, acting as a NO scavenger during nodule development and nitrogen fixation. However, regulators responsible for Lb expression and modulation of Lb activity have not been characterized. In our previous work, a Jasmonate-Zim-domain (JAZ) protein interacting with a Lb (AsB2510) in Astragalus sinicus was identified and designated AsJAZ1. In this study, the interaction between AsJAZ1 and AsB2510 was verified using a yeast two-hybrid system and in vitro Glutathione S-transferase (GST) pull-down assays, resulting in identification of the interaction domain as a TIFY (previously known as zinc-finger protein expressed in inflorescence meristem, ZIM) domain. TIFY domain is named after the most conserved amino acids within the domain. Bimolecular fluorescence complementation (BiFC) was used to confirm the interaction between AsJAZ1 and AsB2510 in tobacco cells, demonstrating that AsJAZ1-AsB2510 interaction was localized to the cell membrane and cytoplasm. Furthermore, the expression patterns and the symbiotic phenotypes of AsJAZ1 were investigated. Knockdown of AsJAZ1 expression via RNA interference led to decreased number of nodules, abnormal development of bacteroids, accumulation of poly-x-hydroxybutyrate (PHB) and loss of nitrogenase activity. Taken together, our results suggest that AsJAZ1 interacts with AsB2510 and participates in nodule development and nitrogen fixation. Our results provide novel insights into the functions of Lbs or JAZ proteins during legume-rhizobia symbiosis.